2015
DOI: 10.5603/fm.2015.0025
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and clinical significance of the maxillary nerve: a literature review

Abstract: (Folia Morphol 2015; 74, 2: 150-156)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…The maxillary nerve is a purely sensory nerve supplying the upper dentition and gingiva, hard and soft palate mucosa, nose, upper lip, maxillary sinus, as well as many adjoining structures [37]. It innervates only the structures of the maxillary process in fetal life and further extends to include also the frontonasal process during embryological development [37]. The anatomical variations may cause anesthesia failure or surgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…The maxillary nerve is a purely sensory nerve supplying the upper dentition and gingiva, hard and soft palate mucosa, nose, upper lip, maxillary sinus, as well as many adjoining structures [37]. It innervates only the structures of the maxillary process in fetal life and further extends to include also the frontonasal process during embryological development [37]. The anatomical variations may cause anesthesia failure or surgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…Infraorbital groove (IOG), located on the inferior wall of the orbit and at the orbital surface of the body of maxilla, begin from the inferior orbital fissure posteriorly and continues as infraorbital canal (IOC) anteriorly and IOC opens to the middle of the face through the infraorbital foramen (IOF). Infraorbital nerve (ION) and vessels pass through IOG, IOC and spread from IOF [70,74]. ION is responsible for the sensory innervation of upper cheek skin, maxillary sinus mucosa, maxillary incisor, canine and premolar teeth, occasionally mesiobuccal root of first molar tooth and adjacent buccolabial gingiva and periostium, the skin and conjunctiva of the inferior eyelid, part of the nose, and the skin and mucosa of the upper lip [52].…”
Section: Introductionmentioning
confidence: 99%
“…Anaesthesia of the ION may be performed on interventions such as surgical procedure of the facial region involving nose soft tissues, cheek, lower eyelid and maxillary premolar, canine and incisive teeth, orbital floor fracture treatment, nasal bone fracture reduction, scar revisions, cosmetic cutaneous procedures and polypectomy [51,55,74]. ION blockage may be performed for trigeminal neuralgia and postoperative pain [2,27].…”
Section: Introductionmentioning
confidence: 99%
“…1). Some researchers have suggested that the fracture of the mandibular ramus is considerably more frequent in individuals with impacted third molars, since they weaken the bone at the site, contributing to a thinning and weakening of the cancellous bone structure [14,30,31].…”
Section: Discussionmentioning
confidence: 99%